Processing and characterisation of MWCNT reinforced aluminum matrix composites - Sridhar, Idapalapati (2011)
Metal matrix composites comprising aluminum matrix and multi-wall carbon nanotubes (MWCNTs) as reinforcements are fabricated using cold uniaxial compaction followed by sintering and cold extrusion as secondary processes. The MWCNTs are pretreated with sodium dodecyl sulfate (SDS) for improved adhesion with aluminum powder. The effect of sintering temperature on the microstructure is explored using differential scanning calorimetric (DSC) spectrum. The tensile yield and ultimate strength of Al/MWCNTs increased to 90% with 2 wt% addition of MWCNTs. Various theories for the strengthening and stiffening of Al/MWCNTs composites are explored.